PENGEMBANGAN PERANGKAT PEMBELAJARAN PADA EDUKASI BAHAYA KEBAKARAN DAN UPAYA PENYELAMATAN DIRI DENGAN METODE PROBLEM BASED LEARNING BERBASIS HIGHER ORDER THINKING SKILLS PADA SISWA KELAS V - Aditya Hermawan; Avanti, Ratu Amalia; Sukarno, Ragil (Jurnal Pendidikan Teknik dan Vokasional, 2021)
This study aims to develop a web-based learning model on the fuel system material and determine the feasibility of the learning model product based on the assessment of 2 material experts, 2 media experts and 30 students at SMK Negeri 54 Jakarta. This research method is Research and Development (R&D) with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The results in this study are a web-based learning model that can be accessed via computers and smartphones with the address https://teknikengine.000webhostapp.com. In this study, it was shown that the level of feasibility of the learning model based on the assessment of material experts from all aspects obtained a percentage of 88.33% which was included in the "Very Eligible" category. Media experts in all aspects obtained a percentage of 85.38% which was included in the "Very Eligible" category and the satisfaction results by students in all aspects obtained a percentage of 89.23% which was included in the "Very Satisfied" category. Thus, the web-based learning model on this fuel system material is "Very Appropriate" to be used as a learning model Keywords: Learning Model Development, Feasibility